Trends of multimorbidity status among the older Chinese population: findings from the Chinese Longitudinal Healthy Longevity Survey 2000 to 2018. Issue 1 (29th November 2022) - Su, Hexuan; Chen, Yuming; Xu, Huiwen; Wang, Kaipeng; Luo, Yan; Xu, Beibei
Abstract: Objectives: This paper aimed to assess temporal trends and risk factors of multimorbidity among older Chinese adults from 2000 to 2018. Methods: A total of 51, 326 participants aged 65–105 from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) 2000–2018 were included. Multimorbidity was defined as the co-occurrence of 2 or more (up to 14) chronic conditions in a single person. The adjusted proportion of the number of chronic conditions by follow-up year was examined and described. The generalized estimating equation model including the natural cubic spline was used to predict the prevalence of multimorbidity. Associated factors were identified using generalized estimating equation models from 2000 to 2018. All analyses were conducted separately in 2 age groups: the young-old group (aged 65–79) and the older-old group (aged 80–105). Results: The adjusted multimorbidity prevalence for the young-old group increased from 23.9% in 2002 to 72.5% in 2014 and remained high at 46.3% in 2018; the adjusted prevalence for the older-old group increased from 63.4% in 2000 to 87.2% in 2011 and remained at 73.0% in 2018. Being female, having fewer educational years, a professional or technical occupation, and a history of smoking or drinking were associated with an increased risk for multimorbidity in young-old group; while in older-old group, being female, current smoker or drinker, and less engagement in social and leisure activity were associated with an increased risk for multimorbidity. Conclusion: The prevalence of multimorbidity first increases and then decreases for both age groups. Management of multimorbidity requires more attention from health policymakers, service providers, and educators of health professionals in China. Health systems should prioritize improving the management of older patients, especially women who have lower education levels.